Analysis of the Quality of Education Services on the Satisfaction of Parents of Students of the Aulady Model Elementary School - Nurul Hidayah; Nila Nurochani; Mulia Amirullah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to determine the level of interest of students' parents and the level of company performance as well as the satisfaction of parents of students with educational services at SD Model Aulady Ciamis. Importance Performance Analysis (IPA) is used to determine the level of importance and performance given by SD Model Aulady. While calculating the satisfaction of parents of students using the customer satisfaction index (CSI). At the level of interest of students' parents, it was found that the teacher's attribute of teaching with discipline and on time was considered the most important with an average value of 4.96. As for the company's performance level, the attribute of teachers mastering learning materials is considered to have the highest performance with an average value of 3.83. Attributes when there is a problem, the teacher always solves it quickly and accurately, students are able to read the Koran using the tamyiz method according to their class level, students are able to carry out obligatory and circumcision prayers along with their readings, and the school has complete facilities to support learning and education, this is indicated by its position in quadrant A (top priority for improvement). The calculation results show that the parents of students/respondents are satisfied with the company's performance with a CSI value of 86.15%.